Physical Therapy and Pulmonary Rehabilitation in Patients with COVID-19 - Шупер, Сергій Вікторович (Український журнал медицини, біології та спорту, 2021)
The global pandemic of the novel coronavirus disease COVID-19 is continueing for the second year, despite tremendous progress in the development and implementation of vaccinations to prevent this disease. The incidence is increasing all over the world, affecting people of different age groups. The inability to predict the severe course of the disease, the development of complications or the so-called "long-COVID" remain one of the most important problems. In patients with COVID-19, damage to the respiratory and cardiovascular systems prevails, manifests itself in the progression of shortness of breath, decrease in blood oxygen saturation and respiratory failure and requires the use of intensive methods of respiratory support, mainly in patients with concomitant diseases such as diabetes mellitus, obesity, coronary heart disease, cancer, chronic obstructive pulmonary disease. COVID-19 reconvalescents, who had significant lung and airway damage, suffer from respiratory complications for a long time due to massive fibrosis of the lung tissue, the development of restrictive respiratory disorders, which significantly impairs the quality of life of such patients. The purpose of the study was to discuss the feasibility and effectiveness of pulmonary rehabilitation and its recommended strategies in patients with COVID-19, based on data from modern literature. The evidence-based rehabilitation process is governed by a functional assessment using the International Classification of Functioning, Disability and Health. The rehabilitation process is based on the strategy of the rehabilitation cycle and consists of sequential stages: assessment, appointment, intervention, quality estimation. Rehabilitation is provided by the multidisciplinary team and begins with a specialized rehabilitation examination, determining the presence or risk of a functional limitation, quantifying them and creating an individual rehabilitation plan. Continuous monitoring of patients' respiratory and hemodynamic parameters before, during and after a physical therapy session is essential to ensure patient safety and assess cardiorespiratory stress in order to optimize an individualized plan and rehabilitation program. Conclusion. Taking into account the phased use of physical therapy and pulmonary rehabilitation, depending on the severity of COVID-19, existing complications and comorbid pathology, a maximally individual syndromic-pathogenetic approach is proposed that realizes the maximum effectiveness of each rehabilitation technique, depending on the patients’ pathological changes, the level of fitness and exercise tolerance
Keywords: COVID-19, physical therapy, pulmonary rehabilitation